Scheme of 5G message system co-construction and sharing - Xiaodan NIU; Chen XU; Jingxia CHEN; Xiangfei JIAO (Dianxin kexue)
With the joint release of “5G message white paper” on April 8, 2020, China’s three major telecom operators have reached a consensus that they will comprehensively upgrade the short message service in the 5G era and create a new business form of 5G message.On the basis of emphasizing the construction of 5G message system, the difficulty of 5G message system carrying the message services of three operators was analyzed under different co construction scope from the technical perspectives of network architecture, interface interoperability and security risk, and finally recommends the construction scheme of co-construction of MaaP, so as to meet the 5G message services development demands of three operators with less implementation cost.